La investigación de empresas - ayer y hoy - Schneider, Erich (1967)
As time goes on, due to the growing specialization and complication of problems, Enterprise Economy is coming to be a special branch of science which, from its beginning, has had an operational character. The difference, however, is not so much due to the latter feature but derives from its problems and methods. Nowadays Enterprise Economy is oriented toward the future, whereas previously it was aimed preferentially toward the past. As regards methods, the difference lies in the growing use of mathematical language which makes it possible to tackle problems formerly not accessible to exact scientific procedures. Nowadays it is focused on the problems of planning which are characteristic of it. By means of examples some short – and long-term planning problems are explained. Starting out from the analysis of COURNOT, of the planning of the "outlet/price" curve, a way is shown towards the methods of lineal and non-lineal programming. The new methods do not replace the marginal analysis which continues as the central instrument, still indispensable also in modern investigation. In an accounting system orientated towards the future, the centre of gravity of planning and planning control necessarily has to lie on the departmental side. A warning is expressed against assigning too much importance to calculating machines and not enough to the investigation of the economic possibilities of electronic equipment. Problems of long-term planning are briefly dealt with such as those discussed in investment theory, expounding the basic methods (capitalization, internal interest, annuities), rejecting as inapplicable more recent attempts to solve the problem of economical yield simultaneously with the problem of liquidity. It is stressed that, not with standing more recent discoveries there still remains a by no means insignificant margin for entrepreneur's skill.